Compreendendo o impacto das diretrizes propostas pela Política Nacional de Práticas Integrativas e complementares em serviços de homeopatia do Sistema Único de Saúde - Lemonica, Renata [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Since its introduction in Brazil in 1843, Homeopathy has presented a unique history with improvements and setbacks. In 2006 the Brazilian Ministry of Health finally introduces the National Policy on Integrative and Complementary Practices (PNPIC, in Portuguese), a set of guidelines aiming to standardize and formalize the practices of Homeopathy, Acupuncture, Herbal Medicine, Hydrotherapy and Anthroposophy offered by the National Health System (SUS, in Portuguese). The aim of this study is to understand the impacts of those guidelines, already in process of consolidation, on Homeopathy service offered by SUS. This is a qualitative study that used the methodological framework of Content Analysis and collected data between 2012 and 2013 through the application of recorded semi-structured interviews that were later fully transcribed and analyzed. Those interviews were conducted with medical coordinator and/or managers of seven Homeopathy Services located in Southeastern Brazil. The analysis of the interviews unveiled themes relating to the formulated questions, revealing perceptions about the impact of each one of the seven PNPIC guidelines related to the homeopathic area. It is possible to observe that, given the peculiar process of construction and structuring of SUS Homeopathic Services both progress and stagnation could be perceived after the introduction of PNPIC. Established goals, formatted templates, guiding actions, publicity and some specific events could be mentioned as some of PNPIC's sensed benefits. On the other hand, it's surprising how it also created frustrated expectations regarding unreleased funding on already established Homeopathy services. Operational barriers can also be perceived, such as: implementation and development of homeopathic care services being still influenced by its managers' personal beliefs; restrict access to homeopathic medicine within the public healthy system; insufficient homeopathy professional ...

Desde sua introdução no Brasil, em 1843, a Homeopatia apresenta uma história peculiar, com avanços e retrocessos no cenário nacional, até que, em 2006, é implantada, pelo Ministério da Saúde do Brasil, a Política Nacional de Práticas Integrativas e Complementares (PNPIC), sendo regida por diretrizes para normatizar e oficializar a prática da Homeopatia, Acupuntura, Fitoterapia, Termalismo e Antroposofia no Sistema Único de Saúde (SUS). Este estudo teve como objetivo compreender o impacto destas diretrizes propostas pela PNPIC em Serviços de Homeopatia do SUS, que já caminhavam em seu processo de consolidação. Tratase de um estudo de abordagem qualitativa, que utilizou o referencial metodológico da Análise de Conteúdo. A coleta dos dados se deu por meio da aplicação de entrevistas semiestruturadas gravadas em áudio e transcritas na íntegra no período entre 2012 e 2013. Foram entrevistados médicos homeopatas coordenadores ou gestores de sete Serviços de Homeopatia da região Sudeste do Brasil. A análise das entrevistas desvelou categorias temáticas referentes às questões formuladas, descortinando as percepções sobre o impacto de cada uma das sete diretrizes, próprias da área homeopática da PNPIC. Pode-se observar que avanços e estagnações foram percebidos após a introdução da PNPIC. Alguns ganhos foram percebidos, como criação de metas, moldes, ações norteadoras, divulgação e eventos específicos. No entanto, chama atenção como a PNIPIC criou uma expectativa nos serviços de Homeopatia já instituídos em relação a financiamentos que não vieram a ocorrer. Obstáculos de ordem operacional ainda se apresentam, como: implantação e ampliação de oferta de atendimento homeopático ainda mostrarem-se dependentes de desejos pessoais de gestores; dificuldade de acesso aos medicamentos homeopáticos na rede pública; pouca oferta de ensino e formação de profissionais homeopatas; pouco ...
Keywords: Homeopatia; Politica de saúde; Cuidados primários de saúde; Medicina Integrativa; Medicina alternativa; Pesquisa qualitativa; Sistema Único de Saúde (Brasil); Primary health care